Thermoelastic properties of microcracked polycrystals. Part II: The case of jointed polycrystalline TATB. (15th December 2018) - Gasnier, Jean-Baptiste; Willot, François; Trumel, Hervé; Jeulin, Dominique; Biessy, Maxime
Abstract: The thermoelastic responses of a cracked TATB polycrystal is modeled using Fourier-based numerical computations and linear homogenization estimates. The numerical method is based on a Fourier scheme previously investigated (Gasnier et al., 2018) and the homogenization schemes include a new self-consistent estimate recently developed for cracked polycrystals. The effect of various populations of intergranular and transgranular microcracks are compared, with special attention to thermal behavior in the percolating regime. A model of micro-cracks is proposed for the TATB material in its initial state and the variations of the volumetric expansion coefficient of the TATB polycrystal under thermal cycles, during cooling and heating, are interpreted.